Visual teams graphic tools for commitment, innovation, & high performance (Hoboken, NJ John Wiley & Sons, 2011)
Graphic tools and strategies for creating teams and sustaining results, whether you are co-located or spread around the world. A design approach is used for building and leading a team.
Includes bibliographical references (p. 265-272) and index.
Keywords: Decision making; Teams in the workplace; Visual communication